Long-Term Tolerance and Recovery of β-Propiolactone/Ultraviolet (βPL/UV) Treated PPSB in Chimpanzees - Stephan, W; Kotitschke, R; Prince, A M; Brotman, B (Thrombosis and Haemostasis, 1981)
Recent experiments have shown that a preparation of PPSB (factor IX concentrate) derived from βPL/UV treated plasma was not infectious in chimpanzees with respect to hepatitis B and non-A, non-B. To answer the question whether the βPL/UV treatment influences the tolerance and efficacy of the PPSB concentrate, long-term application of PPSB-Biotest was carried out in chimpanzees. After 10 applications of 25 U factor IX/kg at weekly intervals, no signs of intolerance were observed by measurement of blood pressure during i. v. application and by means of skin-testing. Determination of coagulation factor activity during the application period revealed the same factor IX recovery at the beginning and at the end of the study.
Keywords: Factor IX concentrate; Immunogenicity; Recovery; β-Propiolactone/Ultraviolet treatment